Vaginal Atresia with Cervical Agenesis, a Rare Congenital Malformation - Regmi, D. R.; Dangal, G.; Karki, A.; Pradhan, H. K.; Shrestha, R.; Bhattachan, K.; Tiwari, K. D.; Bharati, S.; Manandhar, P.; Maharjan, S. (Kathmandu University Medical Journal, 2021)
Congenital vaginal atresia and cervical agenesis is a rare congenital abnormality of the female genital tract. Here we report a case of 15-year old girl with primary amenorrhea with hematometra, presented with lower abdominal mass. She was symptomatic since 5 months and visited local hospital after 4 months of onset of her symptoms when it became severe, where diagnostic laparotomy was performed for suspected Adnexal mass. Intraoperatively adnexal mass was adhered with and extended up to the uterus with 16 weeks size of uterus. Abdomen was closed without any further intervention and was referred to higher center for needful. When she presented to Kathmandu Model Hospital, she was asymptomatic on her 5th post-operative day of laparotomy. We planned for surgical intervention after examination and investigation. Drainage with vaginoplasty with amnion graft with placement of mould was done.